Business Process Management Capabilities for Sustainable Life Cycle Assessment and Reliability-Centered Maintenance Decision-Making Implementations - Chuks Medoh; Chuks Mbohwa (Logistic and Operation Management Research (LOMR), 2025)
Life Cycle Assessment (LCA) and Reliability-Centered Maintenance (RCM) are complementary. Several studies have attempted to integrate both approaches for a more comprehensive assessment of business impacts and to make more sustainable decisions. This article provides a valuable cross-disciplinary contribution by bridging LCA and RCM in the mining sector to explore how the integration of LCA and RCM, based on business process management, affects the sustainability of decision-making. The methodological approaches include bibliometric analysis, Failure Mode and Impact Analysis (FMECA), and simulation. The results show that LCA and RCM are complementary and can be modeled in a holistic way (system theory) based on business process management. Bibliometric analysis confirms the need for more research into digital tools for data integration. Document analysis provides information on how the case study mining industry is performing against global maintenance practices to make more sustainable decisions. The FMECA complements the evaluations provided in this article with qualitative information on the process of operationalization of the proposed integrated framework. FMECA provides data on possible failure modes, their effects, and the criticality of each component. Based on the scenario impact assessment using the key parameters of the LCA and RCM measurements, the simulation results show that the combined business processes of the LCA and RCM can be captured and tested, aimed at quantifying these business processes for the mining sector used as a case study.